Cytoplasmic Sulfurtransferases in the Purple Sulfur Bacterium Allochromatium vinosum: Evidence for Sulfur Transfer from DsrEFH to DsrC - Stockdreher, Yvonne (Public Library of Science, 2012)
While the importance of sulfur transfer reactions is well established for a number of biosynthetic pathways, evidence has only started to emerge that sulfurtransferases may also be major players in sulfur-based microbial energy metabolism. Among the first organisms studied in this regard is the phototrophic purple sulfur bacterium Allochromatium vinosum. During the oxidation of reduced sulfur species to sulfate this Gammaproteobacterium accumulates sulfur globules. Low molecular weight organic persulfides have been proposed as carrier molecules transferring sulfur from the periplasmic sulfur globules into the cytoplasm where it is further oxidized via the “Dsr” (dissimilatory sulfite reductase) proteins. We have suggested earlier that the heterohexameric protein DsrEFH is the direct or indirect acceptor for persulfidic sulfur imported into the cytoplasm. This proposal originated from the structural similarity of DsrEFH with the established sulfurtransferase TusBCD from E. coli. As part of a system for tRNA modification TusBCD transfers sulfur to TusE, a homolog of another crucial component of the A. vinosum Dsr system, namely DsrC. Here we show that neither DsrEFH nor DsrC have the ability to mobilize sulfane sulfur directly from low molecular weight thiols like thiosulfate or glutathione persulfide. However, we demonstrate that DsrEFH binds sulfur specifically to the conserved cysteine residue DsrE-Cys78 in vitro. Sulfur atoms bound to cysteines in DsrH and DsrF were not detected. DsrC was exclusively persulfurated at DsrC-Cys111 in the penultimate position of the protein. Most importantly, we show that persulfurated DsrEFH indeed serves as an effective sulfur donor for DsrC in vitro. The active site cysteines Cys78 of DsrE and Cys20 of DsrH furthermore proved to be essential for sulfur oxidation in vivo supporting the notion that DsrEFH and DsrC are part of a sulfur relay system that transfers sulfur from a persulfurated carrier molecule to the dissimilatory sulfite reductase DsrAB.